DEVELOPMENT OF MULTIMEDIA LEARNING BASED ON MICROSOFT POWER POINTS TO INCREASING THE RESULTS OF CLASS III STUDENTS' VOCATIONAL SCHOOL LEARNING ON THEME 4 "OBLIGATIONS AND RIGHTS" - Irma Arda Shafa Siregar; Deny Setiawan; Daulat Saragi (Sensei International Journal of Education and Linguistic, 2023)
Development of multimedia-based power point learning media to improve PPKn learning outcomes for class III students on theme 4 "My Obligations and Rights". thesis. Basic education. graduate programs. Medan State University. 2023. This study aims to: (1) Describe the development of PPKn multimedia-based learning media for grade III students on theme 4 "My Obligations and Rights". (2) testing the feasibility of PPKn multimedia-based learning media for class III students on theme 4 "My Obligations and Rights". (3) Observing the increase in the results of Civics learning for class III students at SD 101884 Limau Manis. This research is a development research using the ADDIE development model namely Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study were class III students at SD 101884 Limau Manis for the academic year 2022/2023, a total of 23 students. The instruments used were media expert validation questionnaires and PPKn material expert validation questionnaires. The results of this study indicate that (1) the process of developing multimedia-based power point learning media to improve PPKn learning outcomes for class III students in class III on theme 4 "My Obligations and Rights". Multimodal literacy-based literacy activities include five steps, namely: Analyze (analyze), Design (design), Development (development), Implementation (implementation), and Evaluation (assessment). (2) teaching materials for literacy activities based on multimodal literacy are feasible to use with an average percentage reaching 95.05% and the criteria are very feasible. 91 "high" criteria.